2016
DOI: 10.1103/physrevb.94.104203
|View full text |Cite
|
Sign up to set email alerts
|

Transition from stress-driven to thermally activated stress relaxation in metallic glasses

Abstract: The short-range ordered, but long-range disordered structure of metallic glasses yields strong structural and dynamic heterogeneities. Stress relaxation is a technique to trace the evolution of stress in response to a fixed strain, which reflects the dynamic features phenomenologically described by the Kohlrausch-Williams-Watts (KWW) equation. The KWW equation describes a broad distribution of relaxation times with a small number of empirical parameters, but it does not arise from a particular physically motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 53 publications
9
25
1
1
Order By: Relevance
“…38,39 For instance, Qu, et al showed that the brittle titanium-based MG formed one straight shear band while a ductile Pd-based MG formed several curved shear bands in the early stages of plastic deformation. Though our model employs different sample sizes and the relaxation dynamics compared to the experiments, [38][39][40] our simulation results clearly reveal that the spatial correlation of the elastic heterogeneity at the nanoscale can be an important factor that significantly influences the shearbanding process and resultant shear-band patterns, which is consistent with the mechanistic insight provided by several recent works at atomic scale. [41][42][43] The connection between elastic heterogeneity and deformation behaviors of MGs To establish a connection between nanoscale elastic heterogeneity and deformation behaviors of MGs, we perform a statistical analysis of the spatial connectivity of the soft sites, termed soft cluster, in the MGs with different levels of spatial correlation, focusing on the number and size of the soft clusters.…”
Section: A Transition In Shear-band Formation Mechanismssupporting
confidence: 82%
“…38,39 For instance, Qu, et al showed that the brittle titanium-based MG formed one straight shear band while a ductile Pd-based MG formed several curved shear bands in the early stages of plastic deformation. Though our model employs different sample sizes and the relaxation dynamics compared to the experiments, [38][39][40] our simulation results clearly reveal that the spatial correlation of the elastic heterogeneity at the nanoscale can be an important factor that significantly influences the shearbanding process and resultant shear-band patterns, which is consistent with the mechanistic insight provided by several recent works at atomic scale. [41][42][43] The connection between elastic heterogeneity and deformation behaviors of MGs To establish a connection between nanoscale elastic heterogeneity and deformation behaviors of MGs, we perform a statistical analysis of the spatial connectivity of the soft sites, termed soft cluster, in the MGs with different levels of spatial correlation, focusing on the number and size of the soft clusters.…”
Section: A Transition In Shear-band Formation Mechanismssupporting
confidence: 82%
“…In refs. [36] and [37] the stress relaxation curves of several metallic glasses were shown to be composed of two regimes, an initial stress decay assigned to a stress-driven process [36] and a slower stress decay with a thermally activated relaxation time. The two relaxation time scales decouple as temperature decreases [37].…”
Section: Discussionmentioning
confidence: 99%
“…We claim that the KWW behavior for stress relaxation at high strain rate, typical of the relaxation in glasses including metallic ones, is an indication of a “glassy” behavior, and that trueϵ˙ plays here a similar role to the cooling rate trueT˙ in supercooled liquids. It has been found, indeed, that viscous liquids close to their glass transition exhibit non‐exponential relaxation, and the temporal behavior of the response function (e.g., stress in mechanical tests or polarization in response to an applied electric field) is described by a KWW function with β < 1 .…”
Section: Discussionmentioning
confidence: 78%